PERAN INTELIJEN KEAMANAN KEPOLISIAN NEGARA REPUBLIK INDONESIA DALAM UPAYA DETEKSI DINI TERHADAP PENYELENGGARAAN PEMILIHAN UMUM DI KABUPATEN FAKFAK - Ardin, Ardin; Renouw, Dian Mega Erianti; M. Syauta, Novalin (Ensiklopedia of Journal, 2024)
General Elections are proof of the existence of a democratic system in Indonesia in order to create a prosperous and sovereign country, therefore the task of the police is to protect and supervise General Elections which are vulnerable to security, honesty and justice. Based on this, the National Police, through Security Intelligence, has implemented an early detection system so that problems can be avoided during general elections, but in its development there are still problems in holding general elections. This research aims to determine the role of the Republic of Indonesia State Police Security Intelligence in efforts to early detect the implementation of the Fakfak Regency general election and the obstacles faced by the Republic of Indonesia State Police Security Intelligence in efforts to early detect the implementation of the Fakfak Regency general election.The research method used is the empirical normative type, which was carried out in Fakfak Regency, especially in the Security Intelligence section of the Indonesian National Police in Fakfak Regency. Data was obtained through primary data sources and secondary data sources using library study, interview and observation data collection techniques which were then analyzed using qualitative analysis.The results of the research obtained on the role of the Security Intelligence of the Republic of Indonesia State Police in efforts to early detect the implementation of the Fakfak Regency general election, namely that Intelligence plays a role in carrying out security, investigation and mobilization of traditional leaders, religious and community leaders as well as figures who have influence in the jurisdiction Fakfak Police to minimize the potential for disruption to Community Security and Order following the MKRI's PHPU decision. Intelligence also coordinated with Bawaslu regarding the development of the case and mobilized the perpetrators so that they would not do the same thing. Meanwhile, the obstacles faced by the National Police Security Intelligence of the Republic of Indonesia in efforts to early detect the implementation of the Fakfak Regency general election are the lack of openness between election organizers and intelligence agents in providing information on developments in the election, lack of trust in election organizers towards intelligence agents and in the field there are election organizers who are not neutral and lack of infrastructure. Keywords: General Elections, Intelligence, Early Detection